PENERAPAN NILAI-NILAI PENDIDIKAN ISLAM DALAM KEUSAHAWANAN MENURUT AL-QUR'AN SURAH AN-NISA AYAT 29 DAN HADIS RASULULLAH S.A.W. - Ajat Rukajat; Enjay Setiawan, (International Prophetic Conference (SWAN) FPQS USIM, 2024)
This study aims to determine (1) Are There Values of Islamic Education in Entrepreneurship according to QS. An-Nisa Verse 29 and Hadith Rasulullah S.A.W. (2) How are the Constraints in Applicating Islamic Education Values in Entrepreneurship according to QS. An-Nisa Verse 29 and Hadith Rasulullah S.A.W (3) How to application Islamic education values in entrepreneurship according to QS. An-Nisa Verse 29 and Hadith Rasulullah S.A.W. This research was conducted using a qualitative approach that focused on collecting data obtained from observations, interviews and documentation. Source of data used in this study are primary and secondary data, while technical data analysis is done by content analysis. The analysis aims to study documents and literature, present data and draw conclusions descriptively. After the research conducted it was concluded that: The values of Islamic education in Entrepreneurship according to QS. An-Nisa Verse 29 and Hadith Rasulullah S.A.W, includes the value of faith, worship values and moral values. And in entrepreneurship there are values of Islamic education contained in the An-Nisa verse 29 verse there includes the values of glory given by Allah SWT in His Grace. second, Constraints on the application of Islamic Education Values in Entrepreneurship according to Al-Quran Letter An-Nisa verse 29 and Hadith Rasulullah S.A.W, namely: Lack of motivational interest in students, and infrastructure. third, the application of educational values according to Al-Quran letter An-Nisa verse 29 and Hadith, there are majors namely there are majors in catering and marketing and administration, hospitality businesses, restaurant restaurants and mini banks. From the data obtained it can be concluded that the application can be carried out and felt and enjoyed by the surrounding community such as marketing, catering and hospitality majors must accept food orders and hotel and hotel lodging suits, such as cakes that can be felt by all groups, one of them is the community around.